Optimalisasi Branding Melalui Instagram pada SLB Khusus Bina Mandiri Surabaya - Regina Puspita Anindhiya; Thoriq Chusnil Ibad Alifansyah (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
The rapid evolution of social media has made it a significant part of daily life. Instagram, a widely used platform, plays a crucial role in communication, marketing, and branding, particularly among young people. This study focuses on Instagram's effectiveness as a branding tool for educational institutions, with a specific case study on SLB Khusus Bina Mandiri Surabaya. This institution uses Instagram to showcase achievements, communicate with stakeholders, and enhance its public image. The research aims to analyze the impact of Instagram on the institution's branding strategy, exploring both its benefits and challenges. Using qualitative methods, the study collects data through interviews and content analysis of the institution's Instagram account. The findings highlight the importance of social media in educational branding, offering insights for similar institutions seeking to leverage digital platforms for promotion and engagement.